Nutrition Education for Adolescent Girls as a Strategy for Intergenerational Stunting Prevention: A Quantitative Study at SMAN 03 Rumbai - Siska Indrayani; Rina Oktaviana (Yayasan Adra Karima Hubbi, 2025)
Stunting is a chronic nutritional problem with long-term consequences for human capital and is influenced by nutritional conditions across the life course, including adolescence as a critical preconception period. Adolescent girls play a strategic role in intergenerational stunting prevention; however, nutrition literacy in this group remains relatively low. This study aimed to analyze the effect of nutrition education on improving nutrition knowledge among adolescent girls as a preventive strategy for intergenerational stunting among senior high school students.A quasi-experimental study with a one-group pretest–posttest design was conducted. The study participants consisted of 100 female students in grades X and XI from a senior high school in Rumbai, Indonesia, selected using a total sampling technique. Data were collected using a structured nutrition knowledge questionnaire that had been tested for validity and reliability. Data analysis included univariate and bivariate analyses. Normality was assessed using the Shapiro Wilk test, and differences in nutrition knowledge scores before and after the intervention were analyzed using a paired t-test with a significance level of p < 0.05.The mean nutrition knowledge score increased significantly from 65.42 ± 6.12 before the intervention to 81.30 ± 6.05 after the intervention (p < 0.001). A mean difference of 15.88 points indicates a substantial improvement in nutrition knowledge following the nutrition education program. In conclusion, nutrition education is effective in improving nutrition knowledge among adolescent girls and has the potential to serve as an upstream preventive strategy for intergenerational stunting.